Main Controlling Factors of Gas-Water Distribution in Tight Gas Reservoirs of Sulige Gas Field - Yan, Daobo; Xu, Huarui; Wang, Mengqi (International Journal of Natural Resources and Environmental Studies, 2025)
[Objective]Aiming at the complex gas-water relationship faced in the development of the Sulige Gas Field, this study explores the main controlling factors of gas-water distribution in its tight gas reservoirs to provide a theoretical basis for the efficient development of the gas field[1]. [Methods]By analyzing the hydrochemical characteristics of formation water, classifying the types of produced water, and combining parameters such as the chlorosodium coefficient and metamorphism coefficient, the planar distribution characteristics of gas and water were studied. The influencing factors of gas-water distribution were analyzed from aspects including hydrocarbon generation intensity, reservoir physical properties, microstructures, and tectonic features. [Results]The formation water is dominated by CaCl₂type with high salinity (25–32 g/L)[2], which can be divided into three categories: formation water, condensate water, and residual flowback fluid. The gas-water distribution shows spatial heterogeneity: water layers are widely developed in the lower part of He 8 Member, while water layers in Shan 1 Member appear as isolated lens bodies. In areas where the hydrocarbon generation intensity is lower than 20×10⁸ m³/km², water layers account for 65%; the gas displacement efficiency of high-quality reservoirs (porosity >9.32%, permeability >0.67 mD) exceeds 75%[3]; gas enrichment occurs in the overlapping areas of the west-dipping monocline structural high and delta distributary channel sand bodies. [Conclusions]Hydrocarbon generation intensity dominates the macro-differentiation of gas and water, reservoir physical properties determine the micro-occurrence, and tectonic features regulate the gas-water distribution pattern. This study provides a geological basis for the "avoiding water and seeking gas" development strategy of the gas field.